2006
DOI: 10.1038/sj.bjp.0706932
|View full text |Cite
|
Sign up to set email alerts
|

Ru360, a specific mitochondrial calcium uptake inhibitor, improves cardiac post‐ischaemic functional recovery in rats in vivo

Abstract: Background and purpose: The mitochondrial permeability transition pore (mPTP), an energy-dissipating channel activated by calcium, contributes to reperfusion damage by depolarizing the mitochondrial inner membrane potential. As mitochondrial Ca 2 þ overload is a main inductor of mPTP opening, we examined the effect of Ru 360 , a selective inhibitor of the mitochondrial calcium uptake system against myocardial damage induced by reperfusion in a rat model. Experimental approach: Myocardial reperfusion injury was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
129
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(141 citation statements)
references
References 61 publications
10
129
0
2
Order By: Relevance
“…By contrast, treatment with spermine, an activator of the uniporter, led to converse results. MCU was demonstrated to have a regulatory effect in focal cerebral I/R injury, consistent with previous studies (21)(22)(23). In addition, the mechanism by which MCU regulates cerebral I/R injury was hypothesized to be associated with improved mitochondrial energy metabolism due to MCU inhibition.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…By contrast, treatment with spermine, an activator of the uniporter, led to converse results. MCU was demonstrated to have a regulatory effect in focal cerebral I/R injury, consistent with previous studies (21)(22)(23). In addition, the mechanism by which MCU regulates cerebral I/R injury was hypothesized to be associated with improved mitochondrial energy metabolism due to MCU inhibition.…”
Section: Discussionsupporting
confidence: 73%
“…A previous study reported that ΔΨ m decrease was an initiator and was also a consequence of MPTP opening (51). As as an inhibitor of MCU, Ru360 may normalize mitochondrial membrane depolarization by preventing the opening of the MPTP during I/R (22). The results of the present study revealed changes in ΔΨ m , specifically, membrane depolarization during I/R, normalization by RR and accelerated collapse following spermine treatment, that are indicative of the regulatory functions of MCU on ΔΨ m during I/R.…”
Section: +mentioning
confidence: 47%
“…Even if ATP levels are not substantially changed, K ATP channel openers can improve the free energy of ATP hydrolysis, as demonstrated with 31 P-NMR measurements in hypoxic guinea pig hearts (173). It is possible that K ATP channel openers may preserve mitochondrial function during ischemia, similar to the preservation of mitochondrial integrity that is observed with L-type Ca 2ϩ channel blockers (464, 591) and with blockers of the mitochondrial permeability transition pore (180), or by inhibiting Ca 2ϩ uptake into mitochondria (224,254). This putative protective effect may be direct, due to effects of the KCOs on mitochondrial K ATP channels (263) or on the mitochondrial F 1 F 0 -ATPase (11).…”
Section: C) Protection Against the Decline Of Cellular High-energymentioning
confidence: 90%
“…Both increased and reduced mitochondrial Ca 2+ levels have been implicated in mitochondrial dysfunction and increased reactive oxygen species (ROS) production in heart failure (HF) (6,7,(9)(10)(11)(12)(13)(14)(15)(16)(17). Albeit Ca 2+ is required for activation of key enzymes (i.e., pyruvate dehydrogenase phosphatase, isocitrate dehydrogenase, and α-ketoglutarate dehydrogenase) in the tricarboxylic acid (also known as Krebs) cycle (18, 19), excessive mitochondrial Ca 2+ uptake has been associated with cellular dysfunction (14,20).…”
mentioning
confidence: 99%